Exercise-Induced Hyponatremia: An Assessment of the International Hydration Recommendations Followed During the Gran Trail De Peñalara and Vitoria-Gasteiz Ironman Competitions - López de Lara, Diego; Ruiz-Sánchez, Jorge Gabriel; Cuesta, Martín; Seara, Germán; Calle-Pascual, Alfonso Luis; Rubio Herrera, Miguel Ángel; Runkle, Isabelle; Verbalis, Joseph George (Frontiers in Nutrition, 2022)
Introduction Hyponatremia often occurs during the practice of endurance sports. We evaluated the impact on hyponatremia of the hydration recommendations of the Third International Exercise-Associated Hyponatremia Consensus Development Conference 2015 (3IE-AHCD) during the 2017 Gran Trail de Peñalara marathon (GTP) and the Vitoria Gasteiz Ironman triathlon (VGI). Methods Prospective study of GTP and VGI athletes participating in four information sessions in the months prior to the events, to explain that hydration should only be according to their level of thirst, per the recommendations of the 3IE-AHCD. Consenting event finishers were included in final analysis. Pre- and post-race anthropometric and biochemical parameters were compared. Results Thirty-six GTP (33 male) and 94 VGI (88 male) finishers were evaluated. GTP race median fluid intake was 800 ml/h, with 900 ml/h in the VGI race. 83.3% GTPfin and 77.6% VGIfin remained eunatremic (blood sodium 135–145 mmol/L). Only 1/36 GTP and 1/94 VGI participant finished in hyponatremia, both with a sodium level of 134 mmol/L. Fourteen percent of GTP, and 21.2% of VGI participants finished in hypernatremia, with no increase in race completion times. No participating athlete required medical attention, except for musculoskeletal complaints. Pro-BNP and Copeptin levels rose significantly. Changes in copeptin levels did not correlate with changes in plasma osmolality, nor total body water content in impedance analysis. Conclusions Recommending that athletes' fluid intake in endurance events be a function of their thirst almost entirely prevented development of hyponatremia, without induction of clinically significant hypernatremia, or a negative repercussion on race completion times.